Peranan Pimpinan Terhadap Kedisiplinan pada Kantor Urusan Agama (KUA) Peureulak Barat - Nurkadimah; M Djamil (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2021)
Discipline is an important factor in improving performance and efficiency in the office environment, including at the Office of Religious Affairs (KUA) Peureulak Barat. Leaders play a very important role in ensuring discipline is well practiced in the workplace. This study aims to identify the role of leadership in influencing employee discipline at the Peureulak Barat KUA. This research method uses a qualitative approach with interview and observation techniques as a data collection tool. The results of the study show that leaders at the Peureulak Barat KUA have an important role in shaping a culture of discipline in the workplace. Leaders take the initiative to provide discipline training to employees, provide regular feedback, and enforce existing rules. In addition, leaders also show attitudes and behaviors that are consistent with disciplinary values. In conclusion, the role of leadership at the Peureulak Barat KUA is very important in influencing employee discipline. Leaders must take the initiative to build a culture of discipline in the workplace through training, feedback and enforcement. In addition, leaders must be role models by showing attitudes and behaviors that are consistent with disciplinary values. Thus, it can be expected that employee discipline at KUA Peureulak Barat will increase and have a positive impact on office performance and efficiency.